Potentiality of ecological friendly effect on human behavior of green building design / Wan Zuriea Wan Ismail ... [ et.al] - Wan Ismail, Wan Zuriea; lsmail, Faridah (Dr.); Hashim, Ahmad Ezanee (Asso. Prof Dr.); Irfan, Adi (Dr.); Ramele, Rohaslinda (2009)
of benefits gained in its concept. It promotes environmental, economy and aesthetic value. An understanding of how green buildings affect human comfort and human behavior is crucial for its guideline for future implementation. The objectives of this study are to identify the full potential of green roof buildings and problems associated, perceived from facility management point f view in Malaysia. The finding revealed the potential of green buildings in the Malaysian construction industry is increasing as there is awareness on providing a sustainable built environment. They provide leisure and operational space, visual amenities value and health and therapeutic value. Problems identified are the absence of green roofs components, damaged waterproofing, and presence of unwanted animal, water ponding and breeding of mosquitoes. The study point out the benefits, make recommendations on planning and design intent at early stage of green roof development and providing user friendly green buildings.